Drones and the Creative Industry 2018
DOI: 10.1007/978-3-319-95261-1_2
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact of the Creative Industry in the European Union

Abstract: This work analyses the economic impact of the creative industry in the European Union. The paper quantifies the direct and indirect impacts of the creative industry, concluding that they not only have a direct impact on the employment and the production, but also contributes to the technological progress and long-term development of the European Union. Most of this contribution is due to the creative service industries, whereas the direct contribution of the creative manufacturing industries is smaller.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 20 publications
2
16
0
1
Order By: Relevance
“…The gap between the developed countries, as they are often called, and the developing/underdeveloped countries is traceable to the level of creativity and innovation of their industries and employees. There is empirical evidence that international cultures have implications on the creative potentials of citizens and industries across nations (Shao et al, 2019;Liu & Silva, 2018;Boix-Domènech & Rausell-Köster, 2018;Lubart, 2010). Boix-Domènech and Rausell-Köster (2018) quantified the direct and indirect impacts of the creative industry and concluded that the creative industry not only has a direct impact on the employment and production, but also contributes to the technological progress and long-term development of the European Union (EU).…”
Section: Introductionmentioning
confidence: 99%
“…The gap between the developed countries, as they are often called, and the developing/underdeveloped countries is traceable to the level of creativity and innovation of their industries and employees. There is empirical evidence that international cultures have implications on the creative potentials of citizens and industries across nations (Shao et al, 2019;Liu & Silva, 2018;Boix-Domènech & Rausell-Köster, 2018;Lubart, 2010). Boix-Domènech and Rausell-Köster (2018) quantified the direct and indirect impacts of the creative industry and concluded that the creative industry not only has a direct impact on the employment and production, but also contributes to the technological progress and long-term development of the European Union (EU).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also known, from scientific evidence [41], that the size of the cultural and creative sectors has causal effects on productivity, innovation propensity, humanization, and adaptation of the technological model, the health and wellbeing of citizens and their commitment to shared values, and the resilience and capacity for growth of an economic system. Today, the combination of creativity and memory as resources, digitalization as a process to be intensified, and sustainability as the final objective, have become the driving force behind the development of a circular, experiential, collaborative, and more egalitarian economy.…”
Section: Discussionmentioning
confidence: 99%
“…By scanning the results of the majority of recent European studies about CCIs, their contribution in Europe to the national GDP ranges between 5 and 10%. By contrast, when it comes to the regional level, the enthusiasm about the CCIs' potential remains rather limited and not fully utilized [10][11][12][13][14]. In particular, similar to definitional challenges, it is practically impossible to compare the performance of CCIs and their contribution to regional development due to the heterogeneity in their definition, the prevailing differences in national/regional data gathering systems and the allocation of CCIs to different economic output indicators within the economic regional paradigms [15].…”
Section: Introductionmentioning
confidence: 99%